A Simple and Practical Synthetic Method of Carbon Quantum Dots - Guo1, Liang; Zhang1, Yong; Zhang2, Ruo-Xi (Asian Journal of Chemistry, 2014)
Compared with the traditional quantum dots, carbon quantum dots have excellent optical properties, low cell toxicity, good biocompatibility, easy functionalization and low cost, etc. Recently the synthesis of water-soluble carbon quantum dots have attracted more and more attention of researchers. This experiment used nitric acid and hydrogen peroxide as mixed oxidants to activate commercial carbon to synthesize water-soluble fluorescent carbon dots. We investigated the effect of different factors on the fluorescence intensity of carbon dots. Under the optimal conditions, the particle size of carbon dots is about 5 nm, the fluorescence intensity is high and soluble in water, the fluorescence of carbon dots of surface modification is stronger and more stable. We also found that hydrogen peroxide contributed the synthesis of carbon dots. The synthesis method is very simple, low cost, without expensive and large equipment and owns high practicability.